Taking land reform seriously: from willing seller-willing buyer to expropriation - Dlamini, Siphiwe (Centre for Law and Society, 2026)
This dissertation is concerned with the appropriateness and effectiveness of the South African government's policy and approach to land redistribution. It reviews the willing seller-willing buyer approach to land redistribution and assesses its effectiveness and highlights its strengths and weaknesses. This will include an examination of its implementation by two other countries (namely Namibia and Zimbabwe) in the region that have faced similar land issues. in order to determine whether it is an appropriate approach for South Africa. Zimbabwe and Namibia are ideal comparisons as they are neighbouring countries (with similar agricultural sectors) that are also implementing land redistribution at the same time that South Africa is. Namibia, which once formed a part of South Africa (South West Africa), is going through land reform at the same time as South Africa, while the Zimbabwean process began earlier. The fact that both countries also relied on the market-based willing seller-willing buyer principle provides a unique opportunity for the South African government to learn from the experiences of these two countries, while they still manoeuvre through the issues related to the approach. This will enable a determination of whether the willing seller-willing buyer policy is an appropriate basis for South Africa's redistribution programme or whether an expropriation-based approach would prove to be a more effective option.